High prevalence of constitutional BRCA1 epimutation in patients with early-onset triple-negative breast cancer - Mathias Schwartz; Sabrina Ibadioune; Hélène Delhomelle; Solenn Barraud; Sandrine M. Caputo; Olfa Trabelsi-Grati; Marie-Charlotte Villy; Anthony Laugé; Roseline Tang; Etienne Rouleau; Emmanuelle Mouret-Fourme; Dominique Stoppa-Lyonnet; et al. (Clinical Epigenetics)
Abstract Between 5 and 8% of the general population carry a constitutional methylation of the BRCA1 promoter (“epimutation”). Several studies have suggested that these BRCA1 epimutations confer an increased risk of breast cancer, in particular triple-negative breast cancer (TNBC), with an earlier onset than in the general population. However, those studies relied on very few patients with early-onset TNBC. Using specific Methylation-Sensitive High-Resolution Melting, we assessed BRCA1 epimutation prevalence in a large cohort of 112 early-onset (≤ 30 years-old) TNBC patients with no genetic cancer-predisposing pathogenic variants (PVs). We compared this cohort to 87 early-onset TNBC patients carrying cancer-predisposing PVs and to 93 late-onset (≥ 70 years-old) TNBC with no cancer-predisposing PVs. We observed a high prevalence of BRCA1 epimutation in blood cells from early-onset TNBC patients with no cancer-predisposing PVs (38/112, 33.9% [95% confidence interval: 25.4–43.6%]) as compared to early-onset patients with cancer-predisposing PVs (1/87, 1.1% [0.1–7.1%], p value < 0.001) and late-onset patients (11/93, 11.8% [6.3–20.6%], p value < 0.001). These differences remained significant when restricting to epimutations with low variant epiallele frequencies (VEF under 1%). Our results highlight the role of constitutional BRCA1 epimutations in early-onset TNBC risk and call for their integration into multifactorial models used to compute personalized breast cancer risk.